2013
DOI: 10.1021/ef4004768
|View full text |Cite
|
Sign up to set email alerts
|

Model Water-in-Oil Emulsions for Gas Hydrate Studies in Oil Continuous Systems

Abstract: Stable water-in-oil emulsions with water volume fraction ranging from 10 to 70 vol % have been developed with mineral oil 70T, Span 80, sodium di-2-ethylhexylsulfosuccinate (AOT), and water. The mean size of the water droplets ranges from 2 to 3 μm. Tests conducted show that all emulsions are stable against coalescence for at least 1 week at 2 °C and room temperature. Furthermore, it was observed that the viscosity of the emulsion increases with increasing water volume fraction, with shear thinning behavior ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…1 The aggregation and accumulation (or bedding) of hydrates in pipelines can lead to pipeline blockage, resulting in catastrophic operational failures and safety hazards to personnel and equipment. 3 Over the past decade, a four step conceptual model ( Fig. maintaining flow in the pipeline) challenge in oil and gas pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…1 The aggregation and accumulation (or bedding) of hydrates in pipelines can lead to pipeline blockage, resulting in catastrophic operational failures and safety hazards to personnel and equipment. 3 Over the past decade, a four step conceptual model ( Fig. maintaining flow in the pipeline) challenge in oil and gas pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Finding technological and technical solutions aimed to tackle with complex obstructions requires fundamental studies in the fi eld of phase transitions and hydrate growth kinetics in systems constituted by paraffi n deposits and water. However, an analysis of modern literature concerned with this problem demonstrated that studies of gas hydrates are concentrated on theoretical and experimental analyses of the thermodynamics and growth/dissociation kinetics of methane hydrates in water-oil emulsions of various compositions [3][4][5][6][7][8][9][10][11][12][13][14], with the processes of hydrate formation in natural gas mixtures in paraffi n and water deposits still remaining unstudied. Our communication presents data on the thermobaric conditions and kinetic of natural gas hydrate formation in systems composed in various proportions from commercial Asphaltene-Resin-Paraffin Deposits (ARPDs) of the paraffi nic type and water.…”
mentioning
confidence: 99%
“…The experimental data obtained in this work was correlated with the equilibrium conditions of used NG hydrate formation, that were calculated by the procedure elaborated by E. Dendy Sloan ( Figure 6). 27 As a comparison, the figure shows the results of the study of this NG hydrate formation in systems based on distilled water (points 1-4) and in systems that consist of paraffin and water (points [13][14][15][16][17][18], that were published in ref.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, gas hydrates formation significantly complicates the processes of production, transportation, storage and treatment of oil. Analysis of the literature regarding this issue has shown that, both abroad 9,[11][12][13][14][15] and in Russia, 16,17 the majority of conducted experimental DSC studies of hydrate formation in water-oil emulsions refer to the study of methane hydrate formation, and hydrate formation of complex gas mixtures in oil/water systems was not considered actually.…”
Section: Introductionmentioning
confidence: 99%